Fractional laser therapy – the next step in alleviating the symptoms of skin aging (own observations) - Halbina, Adam; Trznadel-Grodzka, Ewa; Rotsztejn, Helena (Menopause Review/Przegląd Menopauzalny, 2014)
Skin aging is a natural process of the skin, which accelerates in menopause and is additionally intensified by accumulating effects of repeated exposure to solar UV radiation and other external factors. Anti-aging skin treatment and constant improvement of its methods have become an important area of current research. The need to apply effective skin anti-aging methods that minimize traumatization resulted in the development of fractional laser technology delivering a laser beam to microscopic column skin zones in order to achieve skin photo-remodeling.